Climatic factors associated with economic determinants significantly affect the spread of COVID-19 in tropical Brazil - Prata, David; Rodrigues, Waldecy; Queiroz Trevisan, Daniela Mascarenhas de; Camargo, Wainesten; Frizzera, Humberto; Carvalho, Rafael; Barbosa, Gentil; Alvares, Clayton [UNESP]; Moreira, Marina F.; De Souza Bermejo, Paulo H. (Elsevier, 2022)
Objective: This study investigates the spatial differences in the occurrence of COVID-19 in Brazilian Tropical Zone and its relationship with climatic, demographic, and economic factors based on data from February 2020 to May 2021. Methods: A Linear Regression Model with the GDP per capita, demographic density and climatic factors from 5.534 Brazilian cities with (sub)tropical climate was designed and used to explain the spread of COVID-19 in Brazil. Main results: The model shows evidence that economic, demographic and climate factors maintain a relationship with the variation in the number of cases of COVID-19. The Köppen climate classification defines climatic regions by rainfall and temperature. Some studies have shown an association between temperature and humidity and the survival of SARS-CoV-2. In this cohort study, Brazilian cities located in tropical regions without a dry season (monthly rainfall > 60 mm) showed a greater prevalence than in cities located in tropical regions with a dry season (some monthly rainfall < 60 mm). Conclusion: Empirical evidence shows that the Brazil's tropical-climate cities differ in the number (contamination rate) of COVID-19 cases, mainly because of humidity. This study aims to alert the research community and public policy-makers to the trade-off between temperature and humidity for the stability of SARS-COV-2, and the implications for the spread of the virus in tropical climate zones.
Keywords: Brazilian tropical zone; Climate; COVID-19; Demographic; Economic; SARS-CoV-2